QARAQALPAQ XALÍQ DÁSTANLARÍNDA TÚS MOTIVINIŃ IZERTLENIW TARIYXÍ - Kulımbetova, A.K. (SCIENCE and SOCIETY, 2025)
The article examines the history of studying the dream motif in Karakalpak folk epics, its semantic layers, and symbolic meanings. The research analyzes the ancient origins of the dream motif, its transformation during the Soviet era, and the processes of revival in the independence period. Using a comparative-typological approach, the dream motif in the Karakalpak epic tradition is compared with similar motifs in the epics of other Turkic peoples, identifying its national features and poetic characteristics. The findings reveal that the dream motif in Karakalpak epics serves not only as a literary device for plot development but also as a significant cultural code that reflects the people’s cosmogonic worldview, religious beliefs, and historical-cultural memory.
Keywords: karakalpak folk epics; dream motif; mythopoetics; archetype; symbol; cosmogony; comparative-typological approach; national identity; folklore studies